A carbon-doped lithium manganese iron phosphate positive electrode material and preparation method thereof

By introducing carbon doping technology into the lithium manganese iron phosphate positive electrode material, the problem of poor electrochemical performance is solved, and the effect of improving the specific capacity, cycle performance and rate performance of the material is achieved.

CN119252906BActive Publication Date: 2025-03-25HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411768512.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-25
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode materials have poor electrochemical performance, low electronic conductivity and lithium ion diffusion rate, resulting in low charge and discharge capacity and poor rate performance.

Method used

The carbon source is obtained by ultrasonic dispersing and drying of silicon carbide and carbon fibers, and then depositing natural gas as carbon source gas at high temperature and heat treatment. Then, the lithium source, iron source, manganese source, phosphorus source and carbon source are mixed in a specific molar ratio, grinding, spray drying and sintering, and carbon doped lithium manganese iron phosphate positive electrode material is prepared.

Benefits of technology

The particle size and morphology of lithium manganese iron phosphate are effectively regulated, the specific capacity of the material, the charge and discharge cycle performance and the high-rate charge and discharge performance are improved, and the internal resistance of the battery is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion battery positive electrode materials, and provides a carbon-doped lithium iron manganese phosphate positive electrode material and a preparation method thereof. The preparation method comprises the following steps: S1, adding silicon carbide into deionized water, ultrasonically dispersing, adding carbon fiber, continuing ultrasonic oscillation for 6-8 hours, placing in a drying box for drying at 80-120°C, then using natural gas as a carbon source gas, depositing at 980-1020°C for 190-200 hours, and then heat-treating at 2000-2100°C to obtain a carbon source; S2, adding a lithium source, an iron source, a manganese source, a phosphorus source and the obtained carbon source into deionized water, mixing, and obtaining a slurry; S3, grinding and spray-drying the obtained slurry to obtain a lithium iron manganese phosphate precursor; S4, sintering the obtained lithium iron manganese phosphate precursor under an inert atmosphere to obtain a carbon-doped lithium iron manganese phosphate positive electrode material, which has excellent specific capacity, charge and discharge cycle performance and high rate charge and discharge performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery positive electrode materials, and in particular relates to a carbon-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion battery is one of the common chemical power sources. It has the advantages of high specific energy, high specific power, long cycle life, and no memory effect. It is an ideal power source for electric vehicles, digital products, and various power tools. Lithium iron manganese phosphate is a positive electrode active material for lithium-ion batteries. Like lithium iron phosphate, lithium iron manganese phosphate also belongs to the phosphate positive electrode active material. It has the advantages of good cycle performance, excellent safety performance, and environmental friendliness. Common synthesis methods of lithium iron manganese phosphate include high-temperature solid phase method, hydrothermal method, and sol-gel method.

[0003] At present, the main reason restricting the large-scale application of lithium manganese iron phosphate is that its electronic conductivity and lithium ion diffusion rate are worse than lithium iron phosphate, resulting in extremely low charge and discharge capacity and poor battery rate performance. In order to improve the lithium ion transmission efficiency and electronic conduction efficiency, the size of lithium manganese phosphate particles must be reduced to nanometer scale, but the traditional solid phase reaction method is difficult to obtain lithium manganese iron phosphate nanostructured materials. In addition, lithium manganese phosphate must be iron-doped and effectively carbon-coated to improve the conductivity of the material. Although it has been reported that nano-scale lithium manganese phosphate materials have been obtained by hydrothermal method, sol-gel method and other methods, the preparation method is complicated, the cost is high, and the tap density of the dispersed nanoparticles is very low, resulting in a very low volume energy density, which is not conducive to practical application. In addition, since lithium manganese iron phosphate does not have a good affinity with carbon, the effect of carbon coating in the existing preparation method is generally unsatisfactory. In order to obtain a higher discharge capacity, it is necessary to add a proportion of up to 20-30wt% of carbon, which further reduces the power density of the battery. At the same time, the effect of carbon coating in the existing preparation method is generally unsatisfactory, and the high rate and low temperature performance of the material are also poor.

[0004] Therefore, it is particularly important to obtain lithium manganese iron phosphate positive electrode materials with high rate and excellent electrochemical performance. Summary of the invention

[0005] The object of the present invention is to provide a carbon-doped lithium iron manganese phosphate positive electrode material and a preparation method thereof, so as to solve the technical problem that the electrochemical performance of the lithium iron manganese phosphate positive electrode material in the prior art is poor.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] The first aspect of the present invention provides a carbon-doped lithium iron manganese phosphate positive electrode material, wherein the lithium iron manganese phosphate positive electrode material comprises a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source; the carbon source is prepared by the following steps:

[0008] Add silicon carbide to deionized water, disperse it ultrasonically, add carbon fiber, continue ultrasonic oscillation for 6-8 hours, place it in a drying oven at 80-120°C for drying, then use natural gas as the carbon source gas, deposit it at 980-1020°C for 190-200 hours, and then heat treat it at 2000-2100°C to obtain a carbon source.

[0009] As a further embodiment of the present invention, the usage ratio of silicon carbide, deionized water and carbon fiber is 2-5 g:100 mL:3-5 g.

[0010] As a further solution of the present invention, the particle size of the silicon carbide is 40-45 μm.

[0011] As a further solution of the present invention, the density of the carbon fiber is 0.45-0.50 g / cm 3 .

[0012] As a further embodiment of the present invention, the phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and dipotassium hydrogen phosphate; the manganese source is at least one of manganous sulfate, manganous nitrate and manganous acetate.

[0013] As a further embodiment of the present invention, the iron source is at least one of ferrous sulfate, ferrous chloride, ferrous nitrate and ferrous acetate; the lithium source is at least one of lithium carbonate, lithium nitrate, lithium hydroxide and lithium acetate.

[0014] The second aspect of the present invention provides a method for preparing a carbon-doped lithium manganese iron phosphate positive electrode material as described in any one of the contents of the first aspect, comprising the following steps:

[0015] S1. Add silicon carbide to deionized water, disperse it by ultrasonic, add carbon fiber, continue ultrasonic oscillation for 6-8 hours, place it in a drying oven and dry it at 80-120°C, then use natural gas as a carbon source gas, deposit it at 980-1020°C for 190-200 hours, and then heat treat it at 2000-2100°C to obtain a carbon source;

[0016] S2, adding a lithium source, an iron source, a manganese source, a phosphorus source and the carbon source obtained in S1 into deionized water, mixing to obtain a slurry;

[0017] S3, grinding and spray drying the slurry obtained in S2 to obtain a lithium manganese iron phosphate precursor;

[0018] S4. Sintering the lithium manganese iron phosphate precursor obtained in S3 under an inert atmosphere to obtain a carbon-doped lithium manganese iron phosphate positive electrode material.

[0019] As a further embodiment of the present invention, the molar ratio of the lithium source, iron source, manganese source, phosphorus source and carbon source is 1.0-1.1:x:1-x:y:1-y, wherein 0.4≤x≤0.6, 0.8≤y≤1.

[0020] As a further solution of the present invention, grinding is performed in S3 to a particle size of 250-350 nm.

[0021] As a further solution of the present invention, the sintering temperature in S4 is 550-600° C., the heating rate is 1.5-2° C. / min, and the sintering time is 6-8 h.

[0022] Beneficial effects of the present invention:

[0023] The carbon-doped lithium iron manganese phosphate positive electrode material of the present invention mixes raw materials at the molecular level, so the particle size and morphology of the lithium iron manganese phosphate can be effectively regulated, and the carbon source added to the lithium iron manganese phosphate raw material can effectively inhibit the growth of lithium iron manganese phosphate grains, making the particle size of the material smaller and more evenly distributed, thereby improving the specific capacity, charge and discharge cycle performance and high-rate charge and discharge performance of the lithium iron manganese phosphate positive electrode material.

[0024] In the present invention, silicon carbide is impregnated into carbon fiber to obtain a carbon source. The introduction of silicon carbide improves the disadvantage of rapid oxidation of carbon fiber at temperatures exceeding 500°C, and further in the process of synthesizing lithium manganese iron phosphate, carbon can maintain its original conductive properties, thereby providing a faster transmission path for electrons during battery charge and discharge, reducing the internal resistance of the battery, and improving the rate performance of the battery.

[0025] The invention discloses a method for preparing a carbon-doped lithium iron manganese phosphate positive electrode material. The preparation process is simple and easy to control. The lithium iron manganese phosphate material is dried by a spray drying method, which greatly improves the utilization rate of the raw materials. At the same time, the production energy consumption and raw material costs are low, the production efficiency is high, and the material can be applied to large-scale production. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] This embodiment provides a carbon-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof:

[0029] Its preparation method is:

[0030] S1. Add 2.5 g of silicon carbide (particle size 40 μm) to 100 mL of deionized water, ultrasonically disperse for 30 min, and add 3.5 g of carbon fiber (density 0.45 g / cm 3 ), continue ultrasonic oscillation for 6 hours, place in a drying oven at 80°C for drying, then use natural gas as the carbon source gas, deposit at 980°C for 190 hours, and then heat treat at 2000°C to obtain a carbon source;

[0031] S2, the molar ratio of lithium source, iron source, manganese source, phosphorus source and carbon source is 1.0:0.5:0.5:0.8:0.2, the lithium source, iron source, manganese source, phosphorus source and the carbon source obtained in S1 are added into deionized water, mixed to obtain a slurry;

[0032] S3, grinding the slurry obtained in S2 to a particle size of 250 nm, and spray drying to obtain a lithium manganese iron phosphate precursor;

[0033] S4. Sinter the lithium manganese iron phosphate precursor obtained in S3 under an inert atmosphere at a sintering temperature of 550° C., a heating rate of 1.5° C. / min, and a sintering time of 6 h to obtain a carbon-doped lithium manganese iron phosphate positive electrode material.

[0034] The carbon-doped lithium manganese iron phosphate positive electrode material is prepared through the above steps.

[0035] Example 2

[0036] Compared with Example 1, the only difference is:

[0037] S1. Add 4 g of silicon carbide (particle size 40 μm) into 100 mL of deionized water and disperse it ultrasonically for 30 min. Add 4 g of carbon fiber (density 0.45 g / cm 3 ), continue ultrasonic oscillation for 6 hours, place it in a drying oven at 80°C, then use natural gas as the carbon source gas, deposit it at 980°C for 190 hours, and then heat treat it at 2000°C to obtain a carbon source.

[0038] Example 3

[0039] Compared with Example 1, the only difference is:

[0040] S1. Add 4.8 g of silicon carbide (particle size 40 μm) into 100 mL of deionized water, ultrasonically disperse for 30 min, and add 5 g of carbon fiber (density 0.45 g / cm 3 ), continue ultrasonic oscillation for 6 hours, place it in a drying oven at 80°C, then use natural gas as the carbon source gas, deposit it at 980°C for 190 hours, and then heat treat it at 2000°C to obtain a carbon source.

[0041] Example 4

[0042] Compared with Example 1, the only difference is:

[0043] S2. The molar ratio of the lithium source, iron source, manganese source, phosphorus source and carbon source is 1.0:0.5:0.5:0.95:0.05. The lithium source, iron source, manganese source, phosphorus source and the carbon source obtained in S1 are added into deionized water, mixed, and a slurry is obtained.

[0044] Example 5

[0045] Compared with Example 1, the only difference is:

[0046] S3, grinding the slurry obtained in S2 to a particle size of 350 nm, and spray drying to obtain a lithium manganese iron phosphate precursor.

[0047] Example 6

[0048] Compared with Example 1, the only difference is:

[0049] S4. Sinter the lithium manganese iron phosphate precursor obtained in S3 under an inert atmosphere at a sintering temperature of 600° C., a heating rate of 12° C. / min, and a sintering time of 8 h to obtain a carbon-doped lithium manganese iron phosphate positive electrode material.

[0050] Comparative Example 1

[0051] This comparative example provides a carbon-doped lithium manganese iron phosphate positive electrode material and a preparation method thereof:

[0052] Its preparation method is:

[0053] S1, adding the lithium source, iron source, manganese source and phosphorus source into deionized water in a molar ratio of 1.0:0.5:0.5:1, and mixing to obtain a slurry;

[0054] S2, grinding the slurry obtained in S1 to a particle size of 250 nm, and spray drying to obtain a lithium manganese iron phosphate precursor;

[0055] S3. The lithium manganese iron phosphate precursor obtained in S2 is sintered in an inert atmosphere at a sintering temperature of 550° C., a heating rate of 1.5° C. / min, and a sintering time of 6 h to obtain a carbon-doped lithium manganese iron phosphate positive electrode material.

[0056] The carbon-doped lithium manganese iron phosphate positive electrode material is prepared through the above steps.

[0057] Comparative Example 2

[0058] Compared with Example 1, the only difference is:

[0059] S1. Add 1.5 g of silicon carbide (particle size 40 μm) to 100 mL of deionized water, ultrasonically disperse for 30 min, and add 4 g of carbon fiber (density 0.45 g / cm 3 ), continue ultrasonic oscillation for 6 hours, place it in a drying oven at 80°C, then use natural gas as the carbon source gas, deposit it at 980°C for 190 hours, and then heat treat it at 2000°C to obtain a carbon source.

[0060] Comparative Example 3

[0061] Compared with Example 1, the only difference is:

[0062] S2. The molar ratio of the lithium source, iron source, manganese source, phosphorus source and carbon source is 1.0:0.5:0.5:0.7:0.3. The lithium source, iron source, manganese source, phosphorus source and the carbon source obtained in S1 are added into deionized water, mixed, and a slurry is obtained.

[0063] Application and performance tests were performed on Examples 1 to 6 and Comparative Examples 1 to 3:

[0064] (1) Application: Assembly of lithium manganese iron phosphate button batteries:

[0065] The lithium manganese iron phosphate positive electrode material obtained in the embodiment and the comparative example: SP (carbon black conductive agent): PVDF (polyvinylidene fluoride binder) was homogenized according to a mass ratio of 90:5:5, and then coated on a 20 μm thick aluminum foil and dried to prepare a positive electrode sheet; the obtained positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the PE-PP composite film was used as the battery separator, and 1 mol·L -1 LiPF 6 / (EC+DMC) was used as the electrolyte, in which the volume ratio of EC to DMC was 1:1, and assembled into a CR2032 button cell.

[0066] (2) Test: 1C cycle performance test at 25°C: The lithium manganese iron phosphate button cells in the embodiment and the comparative example were tested using a blue electric tester. The prepared button cells were placed in a high-temperature oven at 25°C for charge and discharge tests. The voltage range was 2.0V-4.35V. 0.1C charge and discharge activation was performed for one cycle. Then, the battery was charged at a constant current and constant voltage of 0.5C, the cut-off current was 0.05C, and the battery was discharged at a constant current of 1C for 100 cycles. The relevant data of the first discharge capacity of 0.1C and 1C and the discharge capacity of the 100th cycle were obtained. The test results are shown in Table 1:

[0067]

[0068] As can be seen from Table 1, the button cell prepared from the lithium iron manganese phosphate positive electrode material in Examples 1-6 has a first discharge specific capacity of up to 164.5 mAh / g at a discharge rate of 0.1C, and a first discharge specific capacity of up to 155.2 mAh / g at a discharge rate of 1C, and can still maintain an excellent discharge specific capacity after 100 cycles. Compared with Example 1, the carbon source prepared in the present invention is not added in Comparative Example 1, the amount ratio of the carbon source prepared in Comparative Example 2 is not within the range specified in the present invention, and the amount ratio of the lithium source, iron source, manganese source, phosphorus source and the obtained carbon source used in Comparative Example 3 is also not within the range specified in the present invention. The 0.1C first discharge capacity, 1C first discharge capacity and 100th cycle discharge capacity of the button cell prepared from the lithium iron manganese phosphate positive electrode material in Comparative Examples 1-3 are all lower than those in Example 1. It can be seen that in the synthesis and preparation process of lithium manganese iron phosphate positive electrode materials, the lithium manganese iron phosphate positive electrode materials have high control requirements on the type of raw materials, the ratio of key elements, the preparation method and process parameters.

[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A carbon-doped lithium manganese iron phosphate positive electrode material, characterized in that: The lithium manganese iron phosphate positive electrode material comprises a lithium source, an iron source, a manganese source, a phosphorus source and a carbon source; the carbon source is prepared by the following steps: Add silicon carbide to deionized water, disperse by ultrasonic, add carbon fiber, continue ultrasonic oscillation for 6-8 hours, place in a drying oven for drying at 80-120°C, then use natural gas as a carbon source gas, deposit at 980-1020°C for 190-200 hours, and then heat treat at 2000-2100°C to obtain a carbon source; wherein the amount ratio of silicon carbide, deionized water and carbon fiber is 2-5g:100mL:3-5g; The molar ratio of the lithium source, iron source, manganese source, phosphorus source and carbon source is 1.0-1.1:x:1-x:y:1-y, wherein 0.4≤x≤0.6, 0.8≤y≤1.

2. The carbon-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The particle size of the silicon carbide is 40-45 μm.

3. The carbon-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The density of the carbon fiber is 0.45-0.50 g / cm 3 .

4. The carbon-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The phosphorus source is at least one of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and dipotassium hydrogen phosphate; the manganese source is at least one of manganous sulfate, manganous nitrate and manganous acetate.

5. The carbon-doped lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The iron source is at least one of ferrous sulfate, ferrous chloride, ferrous nitrate and ferrous acetate; the lithium source is at least one of lithium carbonate, lithium nitrate, lithium hydroxide and lithium acetate.

6. A method for preparing a carbon-doped lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Add silicon carbide to deionized water, disperse it by ultrasonic, add carbon fiber, continue ultrasonic oscillation for 6-8 hours, place it in a drying oven and dry it at 80-120°C, then use natural gas as a carbon source gas, deposit it at 980-1020°C for 190-200 hours, and then heat treat it at 2000-2100°C to obtain a carbon source; S2, adding a lithium source, an iron source, a manganese source, a phosphorus source and the carbon source obtained in S1 into deionized water, mixing to obtain a slurry; S3, grinding and spray drying the slurry obtained in S2 to obtain a lithium manganese iron phosphate precursor; S4. Sintering the lithium manganese iron phosphate precursor obtained in S3 under an inert atmosphere to obtain a carbon-doped lithium manganese iron phosphate positive electrode material.

7. The method for preparing a carbon-doped lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: Grind in S3 to a particle size of 250-350 nm.

8. The method for preparing a carbon-doped lithium manganese iron phosphate positive electrode material according to claim 6, characterized in that: The sintering temperature in S4 is 550-600°C, the heating rate is 1.5-2°C / min, and the sintering time is 6-8h.

Citation Information

Patent Citations

  • Composite positive electrode material of graphene and lithium iron phosphate battery and preparation method thereof

    CN103872287A

  • Silicon-carbon composite material and preparation method thereof, electrochemical device and electronic equipment

    CN118782781A